FEATURES OF IMMUNOLOGICAL CHANGES IN TRANSPLANTATION OF AUTOLOGOUS HEMATOPOIETIC STEM CELLS IN PATIENTS WITH MULTIPLE MYELOMA - Achilova, O.U. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
Intensive treatment of multiple myeloma involves maximum suppression of the tumor clone. The introduction of transplantation techniques into clinical practice has significantly improved the outcomes of multiple myeloma, for which the EBMT research team has developed concepts such as complete and partial remission, progression-free survival and disease-free survival. In this scientific article, we tried to solve the following specific tasks: to study the immunophenotype of plasma cells of the bone marrow of primary patients with multiple myeloma by flow cytometry; to study the immunophenotype of bone marrow plasma cells of healthy donors and compare it with the immunophenotype of primary patients with multiple myeloma; to determine the change in the immunophenotypic characteristics of bone marrow plasma cells in patients with multiple myeloma during treatment: after induction therapy, before and after transplantation of autologous hematopoietic stem cells; to study the qualitative and quantitative composition of plasma cells in the leukoconcentrate collected during the first leukapheresis procedure, and to assess the progression-free survival after transplantation depending on the number of plasma cells transfused.